Surface Palladium rich CuxPdy/carbon catalysts for methanol and ethanol oxidation in alkaline media. (20th August 2015) - Mao, Han; Huang, Tao; Yu, Aishui
Abstract: Here we prepare a series of surface Pd rich Cux Pdy /C catalysts with different Pd to Cu ratios which may be applied in methanol and ethanol oxidation in alkaline media. TEM images show that they are well dispersed on the carbon support and the diameters of Cux Pdy nanoparticles are concentrated on 3–5 nm. XPS results confirm there exist obvious interactive electron effect between Cu and Pd. Electrochemical measurements show the Cux Pdy /C catalysts demonstrate better catalytic activity and stability toward ethanol than that of methanol in alkaline media. Cu1 Pd2 /C stands out from the four as-prepared catalysts, whose forward anodic peak current densities for methanol and ethanol oxidation are about 220 mA mg −1 Pd and 520 mA mg −1 Pd, respectively.